2019
DOI: 10.2298/eka1920039o
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of house prices and fiscal policy shocks in Turkey

Abstract: This study examines the interaction between house prices and government spending, mortgage interest rates, and gross domestic product in Turkey. The ARDL bounds test approach is applied to quarterly data covering the 2010:1-2017:4 period. Findings indicate that there is a statistically significant long-run and shortrun cointegration between the two house price indexes and government spending, mortgage rates, and GDP. An increase in government spending has a statistically significant positive effect on house pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Many studies found out that interest rates are effective on housing inflation or housing prices. This finding is consistent with the following studies that we included in the literature review chapter: Sari et al (2007), Badurlar (2008), Öztürk and Fitöz (2009), Lebe and Akbaş (2014), Akkas and Sayilgan (2015), Dilber and Sertkaya (2016), Afşar (2018), İslamoğlu and Buluş (2018), Yıldırım and Yağcıbaşi (2019), Kılcı (2019) and Karadaş and Salihoğlu (2020).…”
Section: Findings and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Many studies found out that interest rates are effective on housing inflation or housing prices. This finding is consistent with the following studies that we included in the literature review chapter: Sari et al (2007), Badurlar (2008), Öztürk and Fitöz (2009), Lebe and Akbaş (2014), Akkas and Sayilgan (2015), Dilber and Sertkaya (2016), Afşar (2018), İslamoğlu and Buluş (2018), Yıldırım and Yağcıbaşi (2019), Kılcı (2019) and Karadaş and Salihoğlu (2020).…”
Section: Findings and Discussionsupporting
confidence: 89%
“…In the study of İslamoğlu and Buluş (2018), it was observed that there was a negative relationship between house prices and mortgage interest rates for the period 2007:Q1-2017:Q2. Yıldırım and Yağcıbaşi (2019) found that the increase in loan rates in the long term caused an increase in housing prices, albeit small in a study conducted with quarterly data of 2010: Q1-2017: Q4. Kılcı (2019) analyzed the relationship between housing loan interest rates and mortgaged housing sales using the monthly data of 2013:01–2018:12, using the Fourier SHIN cointegration test and the Fourier Granger causality test.…”
Section: Theoretical and Empirical Literaturementioning
confidence: 92%
“…Although the HPI (House Price Index) created by the CBRT is usually used as an indicator of house prices, the price index constructed by the REIDIN company has also been used in a small number of studies (for example, Hepşen and Aşıcı, 2013;Erdem et al, 2013, Coşkun et al, 2020. Some of these studies focus on the relationship between house prices and a particular variable (housing credit rate in Akkaş and Sayılgan, 2015;Akpolat, 2020; construction sector confidence index in Çetin and Doğaner, 2017; inflation rate in Sağlam and Abdioğlu, 2020; real exchange rate in Eryüzlü and Ekici, 2020), while other papers examine the relationship between house prices and a battery of macroeconomic variables (see inter alia, Hepşen and Aşıcı, 2013;Karamelikli, 2016;Dilber and Sertkaya, 2016;Yıldırım and İvrendi, 2017;Akkaya, 2018;Kolcu and Yamak, 2018;Yıldırım and Yağcıbaşı, 2019;Bayır et al, 2019;Gebeşoğlu, 2019;Coşkun et al, 2020;Karadaş and Salihoğlu, 2020). On the other hand, there are also regionallevel studies that can be considered as mezzo-scale (for example, Kayral, 2017;Karaağaç and Altınırmak, 2018;Sağlam and Abdioğlu, 2020).…”
Section: Related Empirical Literaturementioning
confidence: 99%
“…The Bank for International Settlement (2022) further noted that in the third quarter of 2021, global residential property prices accelerated to 5.5% yearly in real terms, the greatest since the eve of the 2007/2008 global financial crisis. The boom and bust of house prices were attributed to changes several monetary policy proxies such as interest rates (Baily et al , 2008; Dieckelmann et al , 2023; Jordà et al , 2015; Dullien et al , 2008; Shi et al , 2014), conditions of obtaining mortgage finance (Karley, 2006; Koblyakova et al , 2021) and other factors such as economic growth (Agnello and Sousa, 2009; Khan et al , 2014; Yildirim and Yağcibaşi, 2019). Given the potential impact monetary policy variables have on residential property prices, the paper addresses the question of how the current monetary policy regime in South Africa has managed to influence residential property prices in the short and long run.…”
Section: Introductionmentioning
confidence: 99%